ANALYSIS OF THE TRANSITIVITY PROCESS IN RECOUNT TEXTS WRITTEN BY ENGLISH EDUCATION THIRD-SEMESTER STUDENTS - Aliana Almira; Hayu Dian Yulistianti (IKIP Siliwangi, 2024)
The purpose of this study is to identify the most common transitivity process and the extent to which students' recount texts implement it. This study analyzed 22 texts that were selected from student-written recount texts..The transitivity process was analyzed by the researcher using a descriptive qualitative method. Six processes were identified by the research's findings: the material process (57%) followed by the mental process (29%), the relational process (4,9%), the verbal process (3,2%), the existential process (3,2%), and the behavioral process (2,7%). The material and mental processes were found to be the most prevalent. Because the text the students wrote was a recount, it suggests that they were aware of the proper format for recount texts. As a result, they concentrated more on how to recount past events and actions.that already took place. Students are competent in using the six different types of procedures, even if they mostly employ material.